Penerapan Model Team Games Tournament (TGT) Berbantuan Quizizz Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas XI SMA Negeri 3 Medan - Indah Aditya Putri; Wilda Wani Siregar; Siti Aisyah (Journal on Education, 2024)
Improving student learning outcomes is one of the main focuses in education, because students will be better prepared to face challenges in the world of work and further education and to continue learning and developing. In reality, in mathematics lessons there are still many students' learning outcomes that are low. This can be seen from the unsatisfactory learning outcomes of students after being given lessons. The solution to this problem is to implement a team games tournament model assisted by Quizzizz. The aim of this research is to describe the improvement in student learning outcomes by using the team games tournament model assisted by Quizzizz. This research is classroom action research carried out in 2 cycles.